Analisis Kesiapsiagaan Masyarakat Terhadap Bencana Gempa - Divya Zahrani Khaerunnisa; Luthfi Akbar Rasyidin; Muhammad Wildan Alginani; Rizky Amelia; Ahmad Fuadin (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Understanding mitigation is important as a preventive measure in disaster preparedness. This research was conducted to analyze community preparedness in facing earthquake disasters. The research method used is descriptive quantitative by combining the results of questionnaires and describing the research results of each question. The Bandung community's preparedness for earthquake disasters is still very poor, especially first aid after natural disasters. Apart from that, the low level of interest in reading means that the people of Bandung are still far from being ready to face disasters